Evaluation of the efficacy of transarterial chemoembolization combined with microwave ablation followed by adjuvant therapy in patients with hepatocellular carcinoma - Men, Bowen; Cui, Huzhe; Han, Zhezhu; Jin, Xiuying; Xu, Qiang; Jin, Yongmin; Piao, Zhengri; Zhang, Songnan (Frontiers in Immunology, 2024)
Objective: This study aimed to explore the efficacy of transarterial chemoembolization (TACE) combined with microwave ablation (MWA) adjuvant to lenvatinib and anti–PD–1 antibodies for patients with hepatocellular carcinoma (HCC). Methods: A retrospective analysis of 67 patients with HCC treated at our hospital between October 2018 and May 2022 was conducted. All patients underwent a combination of TACE and MWA. Among them, 29 received postoperative treatment with molecular–targeted agents, like lenvatinib, along with anti–PD–1 antibodies such as sindilizumab, karelizumab, or tirilizumab. The remaining 38 patients did not receive postoperative systemic therapies, like targeted or immunotherapy. The survival and prognosis of all patients were analyzed. Results: Nine patients in the observation group and 29 patients in the control group experienced recurrence, and the median progression–free survival 1 (PFS1) was not reached ‘Not Applicable’(NA) and 17.05 months (P=0.035), respectively. Failure to combine adjuvant therapy was identified as an independent risk factor for tumor recurrence, and the observation group had a 0.245 times lower risk of recurrence compared to that in the control group (P=0.005). Multivariable Cox regression analysis confirmed that the maximum tumor size, and tumor number were risk factors for tumor recurrence. Patients with a large maximum tumor size had a 1.519 times higher risk of recurrence compared to those with a small maximum tumor size (P=0.006), and patients with a large number of tumors had a 5.978 times higher risk of recurrence compared to those with a small number of tumors (P=0.02). The median PFS2 of the two groups was 11.795 and 21.257 months, respectively, though not statistically significant (P=0.955). However, there was a disparity in the percentage of BCLC stages associated with recurrence between the two groups. In the observation group approximately 22.22% of patients progressed to stage C, while in the control group, this proportion was 34.48%. The observation group exhibited a lower risk of distant metastasis compared to the control group. Conclusion: Adjuvant treatment of HCC following TACE combined with MWA improved PFS and achieved better clinical outcomes compared to that with TACE combined with MWA alone.